Pengembangan Media Pembelajaran Basis Data Berbasis Smartphone Bagi Kelas XI Di SMK Negeri 7 Samarinda - Hendra Yuni Irawan (Pusat Riset dan Inovasi Nasional, 2022)
Smartphones have many advantages, one of which is that users can replace or use a variety of unique applications according to their needs, which can be downloaded in app stores or in the Playstore. The applications are as follows games, social networking, music and others. While Smartphones are flying, it is rare for users to use these smartphones for educational or educational activities.